PHARMACOGNOSTIC AND PHARMACOLOGICAL ASPECT OF BACOPA MONNIERI - A REVIEW - Jain, Pushpendra Kumar; Das, Debajyoti; Jain, Puneet; Jain, Prachi; Jain, Pushpendra Kumar (Innovare Journal of Ayurvedic Sciences, 2016)
It is said that the use of Bacopa monnieri for memory enhancement goes back 3000 years or more in India, when it was cited for its medicinal properties, especially the memory enhancing capacity, in the Vedic texts "Athar-Ved Samhila" (3:1) of 800 B.C. and in Ayurveda. In the folklore of Indian medicine, several herbs have been used traditionally as brain or nerve tonics. One of the most popular of these neurotonics is Bacopa monnieri, a well known memory booster. Brahmi has been administered at religious institutions to help students to enhance their memory for learning ancient, religious hymns. It is also used as cardio-tonic, tranquilizer and sedative, improves process of learning, Restores memory, enhances power of speech and imagination, diuretic and nervine tonic, anti stress, for nervous and mental strain, use in insanity, epilepsy, hysteria, aesthenia, nervous breakdown. It is a small, creeping succulent herb. The leaf and flower bearing stems are 10- 30 cm long and arise from creeping stems that form roots at the nodes with pale blue or pinkish white flowers belonging to Family Scrophulariaceae grown nearly banks of freshwater streams and ponds, paddy fields and other damp places. The chief Phyto-constituents present are brahmine, herpestine, alkaloids and saponins. Keywords: Ayurveda, Brahmi, memory booster, herb, neurotonics, tranquilizer.